The Rotator Cuff Healing Index: A New Scoring System to Predict Rotator Cuff Healing After Surgical Repair. Issue 1 (January 2019) - Kwon, Jieun; Kim, Sae Hoon; Lee, Ye Hyun; Kim, Tae In; Oh, Joo Han
Background: Scoring systems integrating possible prognostic factors and predicting rotator cuff healing after surgical repair could provide valuable information for clinical practice. Purpose: To determine the prognostic factors predictive of rotator cuff healing after surgical repair and to integrate these factors into a scoring system. Study Design: Case-control study; Level of evidence, 3. Methods: The authors reviewed the records of 603 patients who, at least 12 months after primary rotator cuff repair by a single surgeon, had magnetic resonance imaging or computed tomographic arthrography to assess repair integrity. The mean age at the time of surgery was 60 years (range, 39-81 years), and 378 patients were women (62.7%). Previous known or suggested factors affecting cuff integrity were analyzed through univariate and multivariate analyses. Factors identified in the multivariate analysis were integrated in a scoring system based on odds ratios (ORs). Results: The overall healing failure rate was 24%. The following independent risk factors were identified in the multivariate analysis: age >70 years at the time of surgery ( P = .003, OR = 2.71), size of the tear in anteroposterior dimension ( P = .033, OR = 1.94) and retraction ( P = .000, OR = 4.56), fatty infiltration of infraspinatus exceeding grade 2 ( P = .001, OR = 2.91), low bone mineral density (T score ≤ –2.5, P = .04, OR = 1.95), and high level of work activity ( P = .036, OR = 2.18). A 15-point scoring system comprised the following: 4 points for retraction; 3 points for fatty infiltration of infraspinatus; and 2 points for anteroposterior tear size, age, bone mineral density, and work activity, weighted according to multivariate analysis ORs. Patients with ≤4 points had a 6.0% healing failure rate, and those with ≥5 and ≥10 points had 55.2% and 86.2% healing failure rates, respectively. Conclusion: A numerical scoring system including significant clinical and radiological factors was designed to predict healing of the rotator cuff after surgical repair. This scoring system helped predict the adequacy of the repair and assist in deciding the appropriate treatment options.